Potential of Jatropha multifida sap against traumatic ulcer - Basri A. Gani; Abdillah Imron Nasution; Nazaruddin Nazaruddin; Lidya Sartika; Rahmat Kurniawan Alam (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Traumatic ulcer is a lesion in oral mucosa as a result of physical and mechanical trauma, as well as changes in salivary pH. Jatropha multifida sap can act as antimicrobial, anti-inflammatory and re-epithelialization, and can also trigger the healing process of ulcers. Purpose: Research was aimed to determine the potential of Jatropha multifida sap against traumatic ulcer base on clinical and histopathological healing process. Method: This research was conducted laboratory experimental model, with rats (Rattus norvegicus) as the subject as well as Jatropha multifida sap for ulcer healing. Those subjects were divided into four groups: two treatment groups administrated with pellet and Jatropha multifida sap, one group as the positive control group administrated with 0.1% triamcinolone acetonide, and one group as the negative control group administrated with 0.9% NaCl. Ulcer manipulation was used 30% H2O2, and evaluation of ulcer healing was used clinical and histopathological approach. Result: Clinically, the healing process of ulcers in the treatment group with Jatropha multifida sap was faster than that in the positive control group with 0.1% triamcinolone acetonide, indicated with the reduction of the ulcer size until the missing of the ulcers started from the third day to the seventh one (p≤0.05). Histopathologically inflammatory cells (lymphocytes, and plasma cells) declined started from the third day, and the formation of collagen and re-epithelialization then occurred. On the seventh day, the epithelial cells thickened, and the inflammatory cells infiltrated. Statistically, those groups were significant (p≤0.05). Conclusion: Jatropha multifida sap has a significant potential to cure traumatic ulcers on oral mucosa clinically and histopathologically.